QUESTION AND ANSWER RELATIONSHIP AND READING COMPREHENSION DEVELOPMENT AMONG THE SOPHOMORE NURSING STUDENTS - Anas Situmeang; Eko Kristianto; Nelson Pandjaitan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Advent Indonesia, 2011)
The research was administrated to answer the question “is there any significanceimprovement after they used the Question and Answer Relationship reading strategy?”The data were collected through pre-test and post-test, administered to 29 students andthe data was analyzed by using T-test.From the computation of the pre-test and post-test, the result showed that theparticipants’ comprehension achievement was improved through QAR strategy and thescore gained by the participants showed that there was a significant effect of QARstrategy. It is strong enough to improve the students’ reading comprehension. Theachievements showed that mean difference between pre-test and post-test is 8.7. Thetcounted = 6.37 > ttable = with significance level in 0.00. Standard error mean of the pretestis 1.15446 and post-test is 0.77600.The researcher hopes that the finding of present study could give some contribution tothe improvement on the teaching reading especially for the faculty of Education atUniversitas Advent Indonesia.